The legitimising processes of a new regulator: The case of the Australian Charities and Not-for-profits Commission. Issue 5 (20th June 2016) - Artiach, Tracy; Irvine, Helen; Mack, Janet; Ryan, Christine
Abstract : Purpose: – The purpose of this paper is to strengthen the theoretical understanding of the processes through which a new regulator seeks to gain legitimacy within an existing regulatory space. The authors do this by investigating the case of the Australian Charities and Not-for-profit Commission (ACNC). Design/methodology/approach: – Synthesising legitimacy theory with the concept of regulatory space, the authors analyse formal public discourse surrounding the establishment and operations of the ACNC. Findings: – Regulation is essentially a context-bound political process in which a new regulator needs to establish legitimacy to ensure its survival. It must convince its constituents that it has developed processes to operate effectively and professionally in addressing constituents' needs, to bargain authoritatively with other regulators in establishing its operational boundaries, and to engage politically with government and constituents. Over a relatively short time, the ACNC built legitimacy, despite the political threats to its formal regulatory authority. Research limitations/implications: – The conclusions are based on the analysis of one case. There is scope for further investigations of the processes by which new regulators establish their legitimacy in different contexts. Practical implications: – The potential for a political threat to the authority of a new regulator, and the difficulty of achieving regulatory reform, particularly in a federated system such as Australia, highlight the necessity for a new regulator to develop a compelling discourse of legitimacy. Originality/value: – The authors synthesise regulatory space and legitimacy perspectives, contributing to an understanding of the processes of regulation.